AIDS Cholangiopathy - Diagnostic imaging features - Vandana V Ahluwalia; Ankita Chauhan; Prerna Singh Saharan; Shamrendra Narayan (Wolters Kluwer Medknow Publications, 2017)
It is important to emphasize that the presence of intrahepatic or extrahepatic biliary stenotic foci in an HIV-positive patient with low CD4 count suggests a possibility of AIDS-associated cholangiopathy, which may be an indicator of progression of the disease. It presents with a clinical variable presentation, although right upper quadrant pain and fever accompanied by an elevated serum alkaline phosphatase (ALP) level are the most common manifestations. We present a case of a young female patient diagnosed with AIDS cholangiopathy as evidenced by clinical features, altered liver function profile indicating obstructive jaundice, classical imaging features on USG, MRI and MRCP, and very low CD4 count.